SCHOOL, COMPANY AND MUNICIPALITY COLLABORATION IN CAREER EDUCATION - Strods, Gunars (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
This article presents results of implementation of school, company and municipality collaboration model in career education in Latvia. The purpose of the study was to work out and implement an educational model for facilitation of student career choice and learning for working life in general education. Empirical data were collected through student selfassessment questionnaires, student portfolio evaluation and analysis of career counselor’s interview. Data collected in period from September, 2012 till February, 2013. 969 students and 19 counselors were involved in the study. Results indicate positive correlation between student’s future plans and quality of career management skills portfolio. For integration of career education in school learning process career counselor, class teacher and subject teacher collaboration is necessary.